دور التلقي البصري مقارنة بالسمعي في اكتساب اللغة: دراسة وصفية لتحليل تفاعل المتعلم ومستوى الفهم الإدراكي" - Maraj, Fadila Faraj allah Al-Koni (Al-Qurtas, 2025)
Listening comprehension consistently ranks among the most difficult skills for learners acquiring a second language, particularly in English as a Foreign Language (EFL) environments where exposure to authentic spoken English is limited (Vandergrift & Goh, 2021). Many classrooms rely heavily on audio-only recordings for listening practice. While such recordings provide genuine examples of spoken language, they often lack the additional contextual support needed for learners to decode and internalize meaning effectively (Field, 2021). Without visual cues such as facial expressions, gestures, or situational context learners may struggle to grasp nuances or infer meanings, leading to incomplete or incorrect interpretations (Rost, 2019). Visual video materials enrich the learning experience by providing multimodal input. Videos present language alongside facial expressions, body language, and environmental context, offering learners multiple channels through which to process information (Paivio, 2020; Mayer, 2020). This multimodality helps clarify ambiguous spoken language and supports deeper cognitive processing, as learners create connections between verbal and non-verbal cues (Yang & Liu, 2023). Empirical studies have shown that learners engaging with video input demonstrate improved comprehension and retention compared to audio-only learners (Zhang & Hsu, 2021; Chen, Wang, & Zhang, 2021).